Effect of pressure intensity of compression short-tight on fatigue of thigh muscles - Miyamoto, N.; Kawakami, Y. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Existing studies have failed to provide evidence of a positive effect on exercise performance by wearing compression short tights covering only both thighs. This could be due to an inadequate pressure intensity that otherwise has a significant effect if applied on the crucial point in the thigh. This study aimed to examine the effect of pressure intensity of elastic compression short-tights on the metabolic state of thigh muscles during submaximal running.